Reproductive tract infections: a self-reported community based study in urban training health centre area of a tertiary care hospital in Kottayam, Kerala, India - Ramesh, Jeena; Joseph, Jose; V. D., Manjula (International Journal Of Community Medicine And Public Health, 2017)
Background: The burden of reproductive tract infections (RTI) among urban women in the reproductive age group (15-49 years) is usually a hidden issue. Earlier studies from Kerala mainly focused on reproductive morbidity among commercial sex workers. A cross-sectional study was conducted to estimate the prevalence of RTI and its association with potential socio-demographic risk factors, based on self reported symptoms among females in the age group 15- 49 years in the Urban training Health Centre field practice area of Government Medical College, Kottayam. Methods: The study was conducted among 643 women of the reproductive age group by single stage cluster sampling technique. A pretested semi structured interview schedule was used for collecting data on the socio demographic profile, clinical symptoms and associated factors after obtaining informed consent. Univariate analysis was done to find association of RTI with various factors followed by a bivariate analysis using binary logistic regression model. Results: The prevalence of RTI was 11.8%. RTI was significantly associated with age at marriage (p=0.02), age at first child birth (p=0.01), type of family (p=0.002), female education (p=0.001), socioeconomic status (p=0.007) and previous history of RTI in last one year (p<0.01) of which 84.1% women with symptoms of RTI had consulted a health personnel. Conclusions: A low prevalence of self reported symptoms of RTI with a high treatment seeking behavior was observed; attributed to the high female literacy. A comparable prevalence in younger age group of 15-24 years (10.9%) and 25-39 years (12.9%) suggesting equal susceptibility of adolescents to RTI was a notable finding.